Análisis polínico de mieles de los Parques Naturales Sierra Norte de Sevilla y Sierras Subbéticas - Andrés, Cristina; Díez, María José; Terrab, Anass (Lazaroa, 2004)
Andrés, C, Díez, M. J. & Terrab, A. Pallen anatvsis of honevsfrom the Natural Parks Sierra Norte de Sevilla and Sierras Subbéticas. Lazaroa 24: 125-133 (2004). Ten houey samples from differení localíties of ihe Natural Parks Sierra Norte de Sevilla aud Sierras Subbéticas have been studied by light microscopy. The resulis shaw thai the nectar from flowers is ihe main boney saurce in ihe region and thai une sample belong tu the Maurizia Class V, twa tu the Class III, five tu the Class II and twa tu ihe Class 1. 38 pallen types were identified belooging tu 22 families, and five honey samples are multiflural, aud five of the samples was unifloral: dover, lavender, rosemary, sunflower aud viper’s bugloss. Helianthus onnuus, Fcbium sp., Brassicaceae, Lavandula stoecbas, aud Eucalyptus sp. were the main nectar source, while, Cistaceae, T Cytisus scopanius aud others, like Quercas sp., were the main pallen saurce. On the other haud, ihe principal haneydew saurce in both Naturats Parks, Quercus suber aud Q. rorund¡folia, were scantly or notbiog used. diterráneo con precipitaciones medias anuales de